Shadow Economy - Is an Enterprise Survey a Preferable Approach? - Reilly, Barry; Krstić, Gorana (Panoeconomicus, 2018)
The direct approaches to measuring the shadow economy have not been used extensively until very recently. A relatively simple method has been developed (Talis J. Putninš and Arnis Sauka 2015) using an income approach to measuring GDP and exploiting survey data on unreported employee wages and the business income generated by enterprises, which was provided by owners/managers of such enterprises. This paper illustrates the advantages of this approach over indirect ones through applying it to two EU candidate countries. This is first done by measuring the size of the shadow economy and then by providing estimates of the factors which cause enterprises to engage in shadow economic activity. Estimates of these factors suggest a number of policy approaches that could reduce the size of the shadow economy in countries similar to the ones we have used here. Key words: Shadow economy, Unreported income, Enterprises and entrepreneurs. JEL: E26, E25, E01. Siva ekonomija - da li je analiza preduzeća preferirajući pristup? Direktni pristupi za merenje sive ekonomije nisu se intenzivno koristili sve do nedavno. Razvijena je relativno jednostavna metoda (Talis J. Putninš i Arnis Sauka 2015) na bazi pristupa merenju GDP-a i korišćenjem podataka iz ankete o neprijavljenim platama zaposlenih i poslovnim prihodima koji stvaraju preduzeća, a koje su pružili vlasnici/menadžeri takvih preduzeća. Rad ilustruje prednosti ovog pristupa u odnosu na indirektne pristupe u dve zemlje koje su kandidati za članstvo u EU. Pristup podrazumeva merenje veličine sive ekonomije, a zatim pružanje procena faktora koji uzrokuju da se preduzeća uključe u sivu ekonomsku aktivnost. Procene ovih faktora sugerišu brojne političke pristupe koji bi mogli smanjiti veličinu sive ekonomije u zemljama sličnim onima koje smo u ovom radu koristili. Ključne reči: Siva ekonomija, neprijavljeni prihod, preduzeća i preduzetnici.